2018
DOI: 10.1016/j.biotechadv.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor microemboli: Progress in molecular understanding and enrichment technologies

Abstract: Circulating tumor cells (CTCs) and their clusters, also known as circulating tumor microemboli (CTM), have emerged as valuable tool that can provide mechanistic insights into the tumor heterogeneity, clonal evolution, and stochastic events within the metastatic cascade. However, recent investigations have hinted that CTM may not be mere aggregates of tumor cells but cells comprising CTM exhibit distinct phenotypic and molecular characteristics in comparison to single CTCs. Moreover, in many cases CTM demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 170 publications
0
60
0
Order By: Relevance
“…About 10 years earlier, Virchow had detected tumor emboli entrapped in vasculature and proposed the first explanation of cancer dissemination by metastases. These clusters of cells were further described from the 1950s, with strong focus on their metastatic potential as compared to single circulating tumor cells (review in Reference [1]). There is already substantial literature on the molecular mechanisms linked with CTCs generation (review in Reference [2]), involving, for example, major cellular pathways effectors, like Erythroblastosis oncogene B (ERBB) family receptors [3].…”
Section: Introductionmentioning
confidence: 99%
“…About 10 years earlier, Virchow had detected tumor emboli entrapped in vasculature and proposed the first explanation of cancer dissemination by metastases. These clusters of cells were further described from the 1950s, with strong focus on their metastatic potential as compared to single circulating tumor cells (review in Reference [1]). There is already substantial literature on the molecular mechanisms linked with CTCs generation (review in Reference [2]), involving, for example, major cellular pathways effectors, like Erythroblastosis oncogene B (ERBB) family receptors [3].…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is supported by multicolor lineage-tracing experiments in a mouse model of pancreatic cancer [37]. Moreover, intravascular CTC aggregation might be inhibited by the shear forces generated in the bloodstream [38].…”
Section: Are Single Ctcs or Ctc Clusters Involved In Metastasis Formamentioning
confidence: 79%
“…The characteristics of a unique structure of clustered hollow spheroids is described for the first time in this paper. An obvious question is whether anything like it has already been seen in vivo , an inquiry that turns up a surprisingly rich history of research on tumor cell clusters mostly isolated from blood, and stretching back more than 50 years (Hong et al2016;Umer et al,2018). Almost consistently, starting with Watanabe in 1954, researchers have concluded that tumor cell clusters are more likely to contribute to metastases than single tumor cells.…”
Section: Are Clusters Of Hollow Spheroids Involved In Metastases?mentioning
confidence: 99%
“…The relevance of tumor cell clusters in metastases was recently reviewed by Cheung & Ewald (2016) with a model of metastatic dissemination that highlights the activities of clusters of tumor cells that retain epithelial properties. Overall, there appears to be recognition that at least some tumor cell clusters may be more than the sum of their parts relating perhaps to discussions about the distinct phenotypic and molecular characteristics of cells in tumor clusters or microemboli in comparison with single cancer tumor cells (Umer et al,2018).…”
Section: Are Clusters Of Hollow Spheroids Involved In Metastases?mentioning
confidence: 99%